Cause Analysis of Pier Inclination of An Expressway Interchange Bridge: Case Study - Qingsong Fu; Xuefei Shi; Haiying Ma (Applied Sciences, 2022)
An expressway interchange bridge was completed in 2016 in China. In 2019, disease phenomenon, including pier inclination, excessive support slip, and expansion joint damage, were found in the ramp bridge, which influenced the bridge safety and operation. This article conducts a forensic engineering field investigation and uses finite element modeling, revealing the process of disease occurrence according to the displacement cooperation relations in the pier–support–girder region. This research concludes that the main technical causes of the bridge’s disease include: (1) eccentric compression on the pier during construction and operation due to an improper design change and the asynchronous construction process; (2) asymmetric foundation settlement caused by the temporary load during construction and the weight of the filling soil during operation. Finally, the ethical factors leading to the disease are summarized based on technical causes, which can alert professional engineers to problems that should be considered in the design and construction of high-pier bridges with a soft foundation.